Environmental determinants of destination competitiveness and its Tourism Attractions-Basics Context, A-B-C, indicators: a review, conceptual model and propositions - Manrai, Lalita A. (2020)
Purpose: The purpose of this paper is to provide a comprehensive review of the literature and develop a model of the determinants, indicators and effects of destination competitiveness (DC), as well as several propositions. Design/methodology/approach: This study thoroughly reviewed extant literature to develop a conceptual model and propositions. Findings: Two key findings are listed below. First, 12 different environmental factors are identified and 12 propositions are developed linking these environmental factors to DC. Second, a new indicator of DC is developed, namely, Tourism Attractions-Basics-Context (TABC) model. The TABC model is simple and directly taps into the benefits tourists seek in a destination. Research limitations/implications – Directions for future research are discussed in detail in the paper. Practical implications – Managerial implications are discussed in detail in the paper. Originality/value: The extant research on the topic of DC has been rather fragmented and incomplete in scope. The research presented in this paper addresses these limitations.